Hubungan Parenting Orang Tua terhadap Kepercayaan Diri pada Anak Usia Dini di TK Bungong Reudeup Baitussalam Aceh Besar - Fauziah Fauziah; Nurul Amna; Nivi Sara Ivantaya (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Parenting patterns play an important role in children's self-confidence. Parents are the main figures who raise and educate their children, because children who have self-confidence will dare to try new things and are not afraid of failure. The purpose of this study was to determine the relationship between parenting patterns and the self-confidence of early childhood children in Bungong Reudeup Baitusalam Kindergarten, Aceh Besar. This type of research is quantitative research with a descriptive analytical design using the Cross Sectional Study method. Data collection used the PSDQ questionnaire. which was carried out on February 22, 2025 for 1 day. The population used in this study were all early childhood children in Bungong Reudeup Baitusalam Kindergarten, Aceh Besar, totaling 30 people with a sampling technique using the total sampling technique. Data analysis using the Fisher Exact Test showed that there was a significant relationship between parenting patterns and the self-confidence of early childhood children in Bungong Reudeup Baitusalam Kindergarten with a P value = 0.033 <0.05. The results can be concluded that parenting patterns have a significant relationship with the self-confidence of early childhood children at Bungong Reudeup Baitusalam Kindergarten, Aceh Besar 2025. promising parents to apply positive and responsive parenting patterns, loving, consistent and open parenting patterns will increase self-confidence in children because children feel accepted and appreciated.